Literature Survey for IoT Based Smart Home Automation: A Comparative Analysis (International Journal of Innovative Research in Computer Science & Technology, 2021)
Since a few years, smart devices have  become an integral part of our daily lives. As a result, on  smart devices, offering facilities and security is becoming  more important. The goal of this article is to create a home  automation system that works with Android mobile devices.  Wi-Fi allows the mobile device and the system to  communicate with one another. Current studies discusses the IoT-Based Smart Home Automation. Any suitable device  may load the mobile application and interact with the system.  Commands to turn on/off electrical equipment such as lights,  fans, and air conditioners, as well as setting timers, can be  delivered simply and fast from mobile devices through a  simple and pleasant GUI application that is straightforward  to use for any average user. The system then acts and  responds to these orders by performing the tasks specified in  the commands and informing the user of the outcome. Within  Wi-Fi range, the user may also view the result on an Android  mobile application. As a result, developing a home  automation system for a luxury living that strives to create  an advanced home automation system utilizing Wi-Fi  technology is a solid option.
Keywords: Arduino Uno; Automation; Equipment; Home; System